(untitled) (Bangladesh Journal of Pharmacology, 2017)
The present study investigated the effect of H. officinalis essential oil on avoidance memory in chronic stress-induced. Mice were exposed to chronic immobilization stress and were treated with H. officinalis essential oil for 21 days. Memory and learning were measured using shuttle box. The serum levels of corticosterone, malondialdehyde, antioxidant capacity, brain malondialdehyde level and antioxidant capacity were measured. Treatment with 75 mg/kg of H. officinalis essential oil caused a significant increase in t2 duration under chronic stress. Serum and brain malondialdehyde levels significantly decreased under stress treated with 75 mg/kg of H. officinalis essential oil. Brain and serum antioxidant capacity significantly increased under stress treated with 75 mg/kg of H. officinalis essential oil. The group that received 75 mg/kg of H. officinalis essential oil (inside the restrainer) had insignificantly lower serum corticosterone levels. H. officinalis essential oil has anti-anxiety effects and can promote memory and learning under chronic immobilization stress. Video Clip of Methodology: Avoidance memory test (t1): 0 min 44 sec: Click to watch Avoidance memory test (t2): 1 min 2 sec: Click to watch